Christian America and the Kingdom of God - Hughes, Richard T. (Univ. of Illinois Press, 2009)
Introduction : getting our bearings -- Christian America as God's chosen people -- The witness of the Hebrew Bible -- The witness of the New Testament -- Why do we think of America as a Christian nation? -- A fundamentalist vision for Christian America : from the Scopes trial to George W. Bush